Intrinsic Magnetic Properties of a Highly Anisotropic Rare‐Earth‐Free Fe2P‐Based Magnet. (15th October 2021) - He, Yangkun; Adler, Peter; Schneider, Sebastian; Soldatov, Ivan; Mu, Qingge; Borrmann, Horst; Schnelle, Walter; Schaefer, Rudolf; Rellinghaus, Bernd; Fecher, Gerhard H.; Felser, Claudia
Abstract: Permanent magnets are applied in many large‐scale and emerging applications and are crucial components in numerous established and newly evolving technologies. Rare‐earth magnets exhibit excellent hard magnetic properties; however, their applications are limited by the price and supply risk of the strategic rare‐earth elements. Therefore, there is an increasing demand for inexpensive magnets without strategic elements. Here, the authors report the intrinsic highly‐anisotropic magnetic properties of Co and Si co‐doped single crystals (Fe1− y Co y )2 P1− x Si x ( y  ≈ 0.09). Co increases Curie temperature T C ; Si doping decreases magnetocrystalline anisotropy K 1 and also increases T C significantly because of the enhanced interlayer interaction. The maximum room temperature magnetocrystalline anisotropy K 1  = 1.09 MJ m −3 is achieved for x  = 0.22, with saturation magnetization µ 0 M s  = 0.96 T and T C  = 506 K. The theoretical maximum energy product is one of the largest for any magnet without a rare earth or Pt. Besides its promising intrinsic magnetic properties and absence of any strategic elements, other advantages are phase stability at high temperatures and excellent corrosion resistance, which make this material most promising for permanent magnetic development that will have a positive influence in industry and daily life. Abstract : The authors report the intrinsic highly‐anisotropic magnetic properties of Co and Si co‐doped single crystals (Fe1− y Co y )2 P1− x Si x . A maximum room temperature magnetocrystalline anisotropy of 1.09 MJ m –3 is achieved, with a saturation magnetization of 0.96 T and a Curie temperature of 506 K, making this material promising for permanent magnets.